(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article explores effective methodologies aimed at developing special endurance qualities in young basketball players. Given the high-intensity and dynamic nature of basketball, endurance plays a critical role in maintaining performance throughout the game. The research focuses on specialized training programs that enhance aerobic and anaerobic capacity, muscular endurance, and recovery speed. Various methods, including interval training, circuit training, and sport-specific drills, are analyzed for their impact on young athletes. The article also discusses age-appropriate load management and injury prevention strategies. The results highlight that a structured and scientifically grounded approach significantly improves endurance, leading to better athletic performance and reduced fatigue during matches.